Social media’s impact on political campaigns (Herald of Journalism, 2019)
Media has always been considered as the main instrument of communication between government and population. However this communication used to be unilateral and aimed to inform people before the Internet. The Internet and social media in particular created opportunities for bilateral communication of government and population. Thus, users can not only openly discuss one or other political topicbut also influence on outcomes of political campaigns. The main goal of the article is to define how internet users can influence on outcomes of elections through social media and how politicians use social media to pursue their own political goals. Scientific significance of this article is in the compliment it makes to existing concepts of social networks and new media. As a result of conducted study it has become clear that social media is a strong instrument of communication of government and population using which authorities can communicate with target groups immediately and agitate or antagonize. Using comments, blogs, messages and creation of online-communities social media users can respond to actions of politicians, agitate or antagonize. And since these conclusions were made on the basis of study of foreign experience of using socialmedia as a tool of influence on the outcomes of political campaigns, this work is very important from the viewpoint of international journalism. Practical relevance: Social networks and new media are considered as platforms using which anyone can feel themselves journalist and highlight political themes without even having appropriate education. That means that any concerned citizen can influence on the outcome of one or other political campaign, and doing so increase index of democracy and freedom of speech.
Keywords: social media, new media, the internet, political campaigns, elections, politics, communication.